Contamination-free Ge-based graphene as revealed by graphene enhanced secondary ion mass spectrometry (GESIMS). (4th December 2017) - Michałowski, P P; Pasternak, I; Strupiński, W
Abstract: In this study, we demonstrate that graphene grown on Ge does not contain any copper contamination, and identify some of the errors affecting the accuracy of commonly used measurement methods. Indeed, one of these, the secondary ion mass spectrometry (SIMS) technique, reveals copper contamination in Ge-based graphene but does not take into account the effect of the presence of the graphene layer. We have shown that this layer increases negative ionization significantly, and thus yields false results, but also that the graphene enhances, by an order of two, the magnitude of the intensity of SIMS signals when compared with a similar graphene-free sample, enabling much better detection limits. This forms the basis of a new measurement procedure, graphene enhanced SIMS (GESIMS) (pending European patent application no. EP 16461554.4), which allows for the precise estimation of the realistic distribution of dopants and contamination in graphene. In addition, we present evidence that the GESIMS effect leads to unexpected mass interferences with double-ionized species, and that these interferences are negligible in samples without graphene. The GESIMS method also shows that graphene transferred from Cu results in increased copper contamination.